Comparison of the Implementation of the Role of the Family Assistance Team (TPK) in the Prevention and Reduction of Stunting in Pulau Simardan and Bunga Tanjung Villages, Datuk Bandar Timur District, Tanjungbalai City in 2024 - Aisiyah Hasibuan; Rahmad Gurusinga; Ahmad Hafizullah Ritonga (JURNAL KESMAS DAN GIZI (JKG), 2026)
This study aims to compare the implementation of the role of the Family Assistance Team (TPK) in the prevention and reduction of stunting in Pulau Simardan and Bunga Tanjung Villages, and to identify the supporting and inhibiting factors in its implementation. The study employed a qualitative approach with a comparative phenomenological design. Data were collected through observation, document review, and in-depth interviews with 13 informants consisting of TPK cadres, target families, Family Planning Field Officers (PLKB), and neighborhood heads. Data were analyzed thematically and validated through source and method triangulation.The results indicate that TPK has carried out its mentoring functions routinely and systematically, including nutrition and health education, surveillance of at-risk families, facilitation of health service and social assistance referrals, psychosocial support, as well as recording and reporting through the Elsimil application. Home visits were conducted one to three times per month. Differences in regional characteristics influenced implementation strategies, where collective-based approaches were more effective in areas with strong social cohesion, while individual approaches were more suitable in areas with high population mobility. Supporting factors included basic training, the use of digital applications, and support from community leaders. The main obstacles were limited facilities and infrastructure, low incentives, and uneven digital literacy. This study recommends strengthening the technical and institutional capacity of TPK and integrating cross-sector coordination based on local data to enhance the effectiveness of stunting reduction acceleration programs.